Implications of inclusive nation-building policies in Kazakhstan : young Kazakh adults' national identity - Yeskarauly, Bolat (University of Leicester, 2015)
The purpose of this dissertation is to examine the implications of nation-building policies in Kazakhstan for the future of Kazakh identity. To consider the implications of largely inclusive policies, this dissertation investigates how young Kazakh adults, born and raised in different cultural and geographical contexts yet with a shared experience of studying and working in the capital city, perceive ethnic, civic, and cultural categories of national identity. A mixed methods approach is used, incorporating the comparative analysis of quantitative and qualitative data. A sample of 120 males and females aged 22 to 30, graduated from a higher education institution, and currently working in Astana, Kazakhstan, completed a questionnaire assessing subjective perceptions of their national identity. Quantitative data are complemented by qualitative data from 30 participants, providing depth and validity to the questionnaire answers. The young adults’ responses reveal that Kazakhs are becoming less segregated culturally, encouraged by the government’s inclusive form of nation-building, the relocation of the capital city and the economic growth. It is argued that the young adults are Kazakhs not only in blood and colour, but also in taste and perception. The prevalence of civic virtues despite the presence of robust ethnic identification was recognized and the urge to organise social life in terms of sharp nationalist boundaries proved thin. The implications of these findings for nation-building policies are discussed. Efforts should be directed towards introducing the historical inclusivity of Kazakh identity and highlighting the sufficiency of cultural integration of non-titular ethnic groups to become members of Kazakh nation.